Modelling the Impact of Energy Consumption, Natural Resources, and Urbanization on Ecological Footprint in South Africa: Assessing the Moderating Role of Human Capital - Nathaniel, Solomon Prince; Bekun, Festus; Faizulayev, Alimshan (International Journal of Energy Economics and Policy, 2021)
Apart from being the most urbanized and largest emitter of CO2 emissions in Africa, South Africa currently harbours an ecological deficit territory mainly due to its desire to attain more growth with less attention to its natural environment. Since environmental distortions are mainly an outcome of human activities, this study becomes the first to investigate the linkage between natural resource (NR), human capital, energy consumption, and ecological footprint (EF) in South Africa. Findings from the long-run results reveal that energy consumption, natural resource, economic growth, and urbanization add to the EF, while human capital curtails environmental deterioration. The interaction between human capital and urbanization helps in mitigating environmental degradation, which suggests a moderating effect of human capital in urban sustainability. The CCR, DOLS and FMOLS confirm the robustness of the findings. A feedback causality exists between natural resource and economic growth, and between economic growth and EF. Natural resources and urbanization also Granger cause EF. Lastly, policies relating to urban and natural resource sustainability and human capital development are discussed. Keywords: Energy Consumption; Natural Resource; Human Capital; Urbanization; Ecological Footprint; South Africa. JEL Classifications: Q40, Q45, Q32. DOI: https://doi.org/10.32479/ijeep.11099